Hydration of tricalcium aluminate and gypsum pastes on the International Space Station. (24th May 2021) - Collins, Peter J.; Grugel, Richard N.; Radlińska, Aleksandra
Highlights: First tricalcium aluminate and gypsum mixtures studied on the International Space Station. Two different mixture designs were tested at various sample ages. Microgravity leads to unique microstructural development. Gypsum within the mixtures becomes striated in microgravity. Abstract: A microstructural analysis of tricalcium aluminate (C3 A) and gypsum pastes that hydrated in microgravity (10 -6 g relative to Earth's gravity) were studied and compared to identical samples processed in terrestrial gravity (1 g ). The experiments were conducted by astronauts onboard the International Space Station (ISS) to understand the influence that microgravity has on the hydration of the cementitious systems. The samples were either quenched with isopropyl alcohol to track any microstructural differences as a function of time or were left to hydrate for the duration of their presence on the ISS. At early ages, the microgravity samples exhibit a comparatively differing microstructure. The dissolution of the gypsum is influenced by the microgravity environment and exhibits unique features such as heavy striations and, at lower gypsum concentrations, a thin reaction shell outlining the original gypsum morphology that persists through the first day of hydration.